ANALISA PERBEDAAN EFEKTIVITAS RELAKSASI GUIDED IMAGERY DAN PEMBERIAN AROMATERAPI LEMON TERHADAP PENURUNAN NYERI PADA PASIEN CA COLON DI RS MURNI TEGUH - Purba, Giot Marito; Lam Murni Br Sagala (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Pain is a problem that often occurs in cancer patients. Pain can be caused by the cancer itself, the tumor can press or irritate other organs and nerves so that it can cause pain. Pain is also caused by cancer treatments such as surgery, chemotherapy, or radiation therapy. The constant pain felt by patients with this terminal illness can reduce the quality of life and physical function, increase the level of fatigue and interfere with daily and social activities. The aim of the study was to determine the effectiveness of giving lemon aroma therapy in reducing pain in Colon Cancer patients undergoing end-cycle chemotherapy at Murni Teguh Hospital. The research design used in this study was a quasi-experimental design with one group pretest – posttest design. The population in this study were all Colon Cancer patients who visited Murni Teguh Hospital in March - June as many as 250 people. Sampling was carried out using a non-probability sampling technique with a purposive sampling type, namely determining the sample with certain considerations according to the inclusion criteria determined by the total sample of 38 people. The instruments used were observation sheets and a Numerical Rating Scale (NRS) with the Wilcoxon hypothesis test. The results of the study obtained a p value of 0.000 <0.05, meaning that there is effectiveness of giving lemon aromatherapy to reducing pain in Colon Cancer patients undergoing end-cycle chemotherapy at Murni Teguh Hospital. Suggestions for the future are expected to be able to develop research with other non-pharmacological therapies that can reduce pain intensity in colon cancer patients such as Benson relaxation therapy, imagery guides and the need to pay attention to environmental conditions that support therapy, one of which is a calm and comfortable environment. In addition, future researchers can use a control group and can be compared with other aromatherapy.